Developing autonomy for first- year English major students at a university in Vinh through writing Portfolio - Đoàn, Thị Ngọc Mai (2020)
The main aim of the study is investigating the extent to which portfolio writing implementation helps students raise their learning autonomynot only in writing but also in their learning